Designing Information System of Website-Based Presence for Online Seminar in Postgraduate School of Universitas Sebelas Maret Surakarta: Perancangan Sistem Informasi Presensi Berbasis Website Untuk Kegiatan Seminar Online Di Sekolah Pascasarjana Universitas Sebelas Maret Surakarta - Purwanto, Joko; Naury, Chairullah; Pantjarani, Ari (Politeknik Harapan Bangsa Surakarta, 2023)
The problem faced in conducting online seminars at the Postgraduate School of Sebelas Maret University Surakarta (UNS) is the difficulty of recording the attendance of online seminar participants. Currently, the process of recording attendance data for online seminar participants is done using the Google Form application. The use of Google Forms for data collection of seminar participants is considered inefficient. This is because the online seminar committee is still copying data from the Google Form to be compiled into a report on the implementation of the online seminar. Based on the description of the background above, it can be formulated the problem to be solved in this research is